Waveform evaluations subject to hardware impairments for mm-wave mobile communications - Wang, Hua; Chen, Xiaoming; Zaidi, Ali A.; Luo, Jian; Dieudonne, Michael (Wireless networks, 2019)
Millimeter-wave bands are receiving great attention for mobile radio communications due to potential availability of enormous channel bandwidths. Larger channel bandwidths are very important to meet ever increasing data rate and capacity demands of future wireless networks. At high carrier frequencies, transmitted and received signals can suffer from severe hardware impairments. We evaluate the performance of several state-of-the-art waveforms, e.g., Cyclic-Prefix (CP)-OFDM, Windowed (W)-OFDM, Pulse-shaped (P)-OFDM, Universal-Filtered (UF)-OFDM, Filter-Bank Multi-Carrier with Offset Quadrature Amplitude Modulation, and DFT-spread (DFT-s)-OFDM, in the presence of hardware impairments. In particular, waveform comparisons have been evaluated in terms of bit error rate, error vector magnitude, and spectral confinement subject to oscillator phase noise and nonlinear power amplifier. It is observed that all waveforms perform similarly subject to hardware impairments—making CP-OFDM with low complexity filtering/windowing operations an attractive option to improve the spectral confinement. One major drawback of multi-carrier waveforms is the high peak-to-average power ratio (PAPR). Various low complexity PAPR reduction techniques for OFDM have been evaluated subject to hardware impairments. It is observed that in case of nonlinear PA and high power transmission, these simple PAPR reduction schemes can achieve similar performance as compared to DFT-s-OFDM, making OFDM also suitable for coverage limited scenarios where power efficiency is important.